Presentation of Progressive and Resultative Functions of te iru Form in the Basic Japanese Textbook “Situational Functional Japanese” - Hari Setiawan; Ari Artadi (Universitas Diponegoro, 2021)
Many studies regarding the acquisition of te iru focus on the learner’s language output. There are very few researches that focus on textbooks as the input in language studies. There is a possibility that introducing grammatical items in textbooks tends to lead the learners to misuse te iru. It is necessary to clarify the grammatical items' characteristics in the basic level textbooks as a language input. Especially, in the study abroad, such as in Indonesia, non-textbook sources for Japanese input are limited. Therefore Indonesian Japanese learners mostly depend on textbooks. This research will discuss the introduction of te iru in the basic level textbooks from the input viewpoint. This research examines how te iru is introduced in “Situational Functional Japanese”. The data in this research include the main textbook and the grammatical explanation, from which te iru sentences are collected and classified. In order to identify the general tendency of te iru in textbooks, te ita, te inai and subordinate sentences are also included as data. Each textbook recognizes that five usages are introduced in the explanation of SFJ, but only two usages are written in explaining the usage of te iru. Their usage is resultative and progressive. And, te inai and te ita are also introduced in SFJ. Moreover, if we look at the distribution of the example sentences of te iru in SFJ the example sentences can still be found, some of which show an increase in subsequent chapters.